2020
DOI: 10.15255/kui.2019.063
|View full text |Cite
|
Sign up to set email alerts
|

Mikroplastika u morskom okolišu Jadrana

Abstract: Plastika se zbog svoje široke uporabe može naći u svim dijelovima okoliša, gdje štetno utječe na različite sastavnice okoliša, a toksični spojevi koje adsorbira prenose se kroz hranidbene lance te s vremenom dolaze do čovjeka. Odabrana istraživanja u ovom radu usredotočena su na karakterizaciju i kvantifikaciju mikroplastike pronađene u Jadranskom moru kao i na toksičnost mikroplastike. Istraživanja su pokazala da je najviše mikroplastike detektirano u području Sjevernog Jadrana. Provedena ispitivanja ekotoksi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Према количини пластичног отпада, Јадранско море Adriatic Sea is the most polluted in Europe after the northeastern part of the Mediterranean and Celtic Seas. Research has shown that in the northern Adriatic extremely high concentrations of MPs were detected, with an average value of about 406,000 particles / km2, which is among the highest recorded concentrations in the Mediterranean Sea so far [16]. Generally, MPs have become one of the emerging contaminants in the aquatic environment, including rivers, lakes, water treatment plants, and drinking water.…”
Section: извори у водиmentioning
confidence: 99%
“…Према количини пластичног отпада, Јадранско море Adriatic Sea is the most polluted in Europe after the northeastern part of the Mediterranean and Celtic Seas. Research has shown that in the northern Adriatic extremely high concentrations of MPs were detected, with an average value of about 406,000 particles / km2, which is among the highest recorded concentrations in the Mediterranean Sea so far [16]. Generally, MPs have become one of the emerging contaminants in the aquatic environment, including rivers, lakes, water treatment plants, and drinking water.…”
Section: извори у водиmentioning
confidence: 99%
“…Global plastic production has been increasing since the 1950s, reaching 367 million tons in 2020 [ 1 ]. The most frequently produced are polyethylene (PE), polyvinyl chloride (PVC), polypropylene (PP), polystyrene (PS), and polyethylene terephthalate (PET) [ 2 , 3 ]. PS is widely used due to excellent properties such as good mechanical properties, lightweight, versatility, durability, stability, and low cost [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…MPs have a high affinity for toxic pollutants, such as heavy metals, persistent organic pollutants (POPs), polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PBCs), chemical additives, and plasticizers (phthalates), due to their large surface area to volume ratio (He et al, 2021;Razeghi et al, 2021). In addition, MPs can easily be ingested by marine biota, as they are often mistaken for food (Bule et al, 2020). Thus, organisms that ingest such MPs are a threat to the whole food web, including humans (Defontaine et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…
Microplastics (MPs), commonly defined as particles less than 5 mm, are a persistent ubiquitous anthropogenic contaminant that can be found in every environment, making it a global environmental, health, and socioeconomic problem. Due to their high surface area, MPs adsorb toxic pollutants that become bioavailable to organisms upon ingestion as they are often mistaken for food leading to biomagnification (Bule et al, 2020). The sampling area represents the lower part of the Krka River Estuary and is under direct anthropogenic influence from the city of Šibenik runoff waters, nautical and communal ports, city harbor, tourism, mariculture, and fishing.
…”
mentioning
confidence: 99%